The fall of Gondolin - Tolkien, John Ronald Reuel, 1892-1973 (HarperCollins Publishers, 2018)
"The Fall of Gondolin tells of the founding of the Elven city of Gondolin, built in secret by Turgon and his people; of the arrival of Tuor, a prince of the Edain; of the betrayal of the city to Morgoth by Turgon's nephew Maeglin; and of its subsequent destruction by Morgoth's armies. It also relates the flight of the fugitives to the Havens of Sirion, the wedding of Tuor and Idril, as well as the childhood of Eärendil."- Résumé de l'éditeur